Seismic vulnerability assessment based on typological characteristics. The first level procedure "SAVE". Issue 69 (February 2015) - Zuccaro, G.; Cacace, F.
Abstract: In this paper a procedure is described for quick seismic vulnerability assessment according to the EMS 98 classification. The criteria adopted by Ems 98 to assign the typological classes are mainly based on the vertical structure type. The proposed methodology aims to reduce the uncertainty in the class assessment using a set of parameters, related to typological features, that are identified as modifiers of the vulnerability level. The paper shows how the weight of each of these parameters is evaluated through the analysis of the seismic damages recorded during past earthquakes. A synthetic damage parameter is then defined in order to compare the seismic response of different sets of buildings under the same seismic intensity. Finally, the vulnerability assessment obtained on a set of buildings by the application of the methodology is compared with expert evaluations derived from the direct inspections on buildings.